2015
DOI: 10.1002/pon.4055
|View full text |Cite
|
Sign up to set email alerts
|

Poor‐prognosis disclosure preference in cancer patient–caregiver dyads and its association with their quality of life and perceived stress: a cross‐sectional survey in mainland China

Abstract: Background: This study attempted to examine the discordance between family caregivers and cancer patients in their poor-prognosis disclosure preferences in mainland China and then ascertained the associations between quality of life (QoL), perceived stress, and poor-prognosis disclosure preferences.Methods: Six hundred fifty-one pairs of inpatients and their matched caregivers (participation rate = 92.2%) were recruited in this cross-sectional survey. A set of paired self-administered questionnaires were compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…The perceived stress levels of participants were measured by the Perceived Stress Scale-14 Chinese version (PSS-14) [32,33]. The PSS-14 is widely used by psychologists to assess perceived stress levels.…”
Section: Assessment Of Perceived Stressmentioning
confidence: 99%
“…The perceived stress levels of participants were measured by the Perceived Stress Scale-14 Chinese version (PSS-14) [32,33]. The PSS-14 is widely used by psychologists to assess perceived stress levels.…”
Section: Assessment Of Perceived Stressmentioning
confidence: 99%
“…Cancer patients want to know their prognosis given their age, sex, tumour type, tumour stage or setting. 25 A US study of 590 patients with advanced cancer found that 71% wanted to know their life expectancy. 6 Telling advanced cancer patients their prognosis early on can improve their quality of life (QoL), anxiety, how well they assess their own life expectancy and their quality of death, and decrease the use of aggressive treatments near the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…The preference for knowing the diagnosis is also a variable associated with the quality of life of the patients, the results obtained with respect to this relationship being sometimes contradictory. Thus, Nie et al (2016) found that the level of education (β = 4.5, p <.05) and a positive preference for knowing an unfavourable diagnosis (β = 3.8, p <.05) are positively associated with the quality of life of patients, while Papadopoulos et al (2011) found that not knowing the diagnosis seems to have a protective eff ect on the physical and mental health of the patients (β = 7.335, p <.001). Regarding the perception of the disease, according to Richardson, Morton, Broadbent (2016), the quality of life of patients at six months after the diagnosis is positively associated with their perceived control over the disease (β = 1.86, p <.01) and the coherence of the perception of the disease by patients and caregivers (β = 1.8, p <.01), and is associated negatively with patient-caregiver discrepancies related to disease progression (β = -1.93, p <.05), the perception of personal control (β = -1.83, p <.05) and the identity of the disease.…”
Section: Quality Of Life In the Patient The Caregiver And Mutual Inmentioning
confidence: 99%
“…As with patients, their preference for knowing the diagnosis has led to contradictory results. If Nie et al (2016) found that monthly income (β = 1.6, p <.05) and a positive preference for knowing an unfavourable diagnosis (β = 2.5, p <.05) are positively associated with the quality of life of the caregivers, Papadopoulos et al (2011) showed that the patient not knowing the diagnosis seems to have a negative eff ect on the physical and mental health of the caregiver (β = -11.644, p <.001).…”
Section: Quality Of Life In the Patient The Caregiver And Mutual Inmentioning
confidence: 99%